2005
DOI: 10.1007/s10628-005-0075-x
|View full text |Cite
|
Sign up to set email alerts
|

Membranotropic Compounds and Alkaloid Accumulation in Plants

Abstract: The biosynthesis of alkaloids is a complex multiphase dynamic process. Its phases are separated spatially, as a rule, at the cellular or subcellular level and, less frequently, at the organ level. In the first two cases, membrane permeability plays a key role in these processes. However, the role of membranotropic compounds (MTC), affecting membrane permeability, in alkaloid biosynthesis is not well studied. Nothing is also known about the effect of the molecular composition of these compounds.The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Many mechanisms pathways of essential oil/antibiotics synergism include sequential inhibition of common biochemical pathways, inhibition of protective enzymes, combination of membrane active agents, and use of membranotropic agents, these mechanisms leads to enhance the diffusion of other antimicrobials [44][45][46][47]. In addition, recent studies have demonstrated that some plant compounds can effectively inhibit the efflux pumps involved in antibiotic resistance mechanisms [48], which could lead to the restoration of sensitivity to antibiotics and reduce their minimum effective dose and thus their side effects and residues in animal products.…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms pathways of essential oil/antibiotics synergism include sequential inhibition of common biochemical pathways, inhibition of protective enzymes, combination of membrane active agents, and use of membranotropic agents, these mechanisms leads to enhance the diffusion of other antimicrobials [44][45][46][47]. In addition, recent studies have demonstrated that some plant compounds can effectively inhibit the efflux pumps involved in antibiotic resistance mechanisms [48], which could lead to the restoration of sensitivity to antibiotics and reduce their minimum effective dose and thus their side effects and residues in animal products.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the outer membrane of the Gram-negative bacteria is not a predominant factor of their resistance. There are some generally accepted mechanisms of antibacterial interaction that produce synergism, including inhibition of protective enzymes, combination of membrane active agents, sequential inhibition of common biochemical pathways and the use of membranotropic agents to enhance the diffusion of other antimicrobials [17].…”
Section: Libanotis Montana Essential Oilmentioning
confidence: 99%
“…There are some generally accepted mechanisms of antibacterial interaction that produce synergism, including inhibition of protective enzymes, combination of membrane active agents, sequential inhibition of common biochemical pathways, and the use of membranotropic agents to enhance the diffusion of other antimicrobials [23]. The results obtained in the present study indicate that chloramphenicol, not currently used as a therapeutic agent against Gram-negative bacteria, in combination with an appropriate essential oil, has significant antimicrobial activity, especially against Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%